2012
DOI: 10.1111/j.1365-2206.2012.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Searching for effective interventions for foster children under stress: a meta‐analysis

Abstract: Foster children experience a lot of stress because of their life histories and changes in their family circumstances, such as foster care placement. It is important that foster parents recognize the early signs of stress in foster children and learn how to act in a non‐threatening and understanding manner. Family‐based interventions may help in this. In this paper, we report on a meta‐analysis of studies (n= 19) of the effectiveness of such interventions. All studies used a pre‐test/post‐test design. Both prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A series of recent reviews and a meta-analysis on intervention programs for foster families found a wide variety of existing programs (e.g., Incredible years, Parent Child Interaction Therapy (PCIT), Keeping Foster and Kin Parents Supported and Trained (KEEP), see Dorsey et al, 2008). These interventions vary in terms of the moment of intervention (pre-placement training for future foster parents vs interventions during placement), foster-care specificity of the programs (programs specifically developed or adapted for use with foster families vs general programs), focus of the intervention (foster carer, foster child, combination), setting (school, day-care, home), intensity and duration (Dorsey et al, 2008;Leve et al, 2012;Rork & McNeil, 2011;Van Andel, Grietens, Strijker, Van der Gaag, & Knorth, 2014). Moreover, in reviews and metaanalyses the limited empirical evidence and the difficulties with drawing conclusions regarding the effectiveness of the studied programs due to methodological limitations is emphasized (e.g., lack of: rigorous design, small sample size, single informants, lack of information on program fidelity information, lack of long term follow-up studies; Dorsey et al, 2008;Leve et al, 2012;Rork & McNeil, 2011;Van Andel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent reviews and a meta-analysis on intervention programs for foster families found a wide variety of existing programs (e.g., Incredible years, Parent Child Interaction Therapy (PCIT), Keeping Foster and Kin Parents Supported and Trained (KEEP), see Dorsey et al, 2008). These interventions vary in terms of the moment of intervention (pre-placement training for future foster parents vs interventions during placement), foster-care specificity of the programs (programs specifically developed or adapted for use with foster families vs general programs), focus of the intervention (foster carer, foster child, combination), setting (school, day-care, home), intensity and duration (Dorsey et al, 2008;Leve et al, 2012;Rork & McNeil, 2011;Van Andel, Grietens, Strijker, Van der Gaag, & Knorth, 2014). Moreover, in reviews and metaanalyses the limited empirical evidence and the difficulties with drawing conclusions regarding the effectiveness of the studied programs due to methodological limitations is emphasized (e.g., lack of: rigorous design, small sample size, single informants, lack of information on program fidelity information, lack of long term follow-up studies; Dorsey et al, 2008;Leve et al, 2012;Rork & McNeil, 2011;Van Andel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses examining the effectiveness of foster care intervention programs have previously been conducted. In the first meta-analysis Van Andel, Grietens, Strijker, Van der Gaag, and Knorth (2012) included intervention programs that may be helpful for foster parents and children to cope with problem behavior and stress, but that were not necessarily tested in a foster care sample. Their literature search resulted in 19 studies, and results showed significant medium combined effect sizes for improved parenting skills and decreased behavior problems.…”
Section: Previous Meta-analytic Studiesmentioning
confidence: 99%
“…In the current study a series of eight meta-analyses have been performed to examine the effectiveness of parenting interventions in foster and/or adoptive families on sensitive parenting, dysfunctional discipline, knowledge and attitudes, and stress, and on child attachment security, child behavior problems, child diurnal cortisol levels, and placement disruption. Contrary to the meta-analysis of Van Andel et al (2012), the current study included studies with (at least) one intervention and one (randomized) control group that did not consider foster care as type of intervention, and that specifically reported results for foster and/or adoptive parents. In addition, compared to the meta-analysis of Solomon et al (2017), effectiveness studies of interventions working with foster and/or adoptive families were also included if they reported outcomes on parenting stress, child attachment security, children's diurnal cortisol levels, and placement disruption.…”
Section: Current Studymentioning
confidence: 99%
“…Transferring generic parenting skills to everyday life in a complex home environment can prove to be difficult. Fostering is a challenging task and each individual child requires tailored parenting approaches (Van Andel et al, ). In FT, carers are specifically asked not to use FT skills in daily life until they have had ample time to practise and achieve success in using these skills in the special play times.…”
Section: Key Learning Points For Practicementioning
confidence: 99%